A 'Get‐Save‐Return' process continuum runs on phosphorus economy among subtropical tree species. (24th January 2023) - Jiang, Lei; Wang, Huimin; Li, Shenggong; Dai, Xiaoqin; Meng, Shengwang; Fu, Xiaoli; Yan, Han; Zheng, Jiajia; Ma, Ning; Kou, Liang
Abstract: Plants allocate nutrients to new leaves via making a cost–benefit trade‐off between root nutrient absorption ('get') and leaf nutrient resorption ('save'). This active trade‐off in nutrient acquisition pathways may cause a passive trade‐off between resorption and decomposition ('return'). However, whether these nutrient‐associated processes are linked and form a 'get‐save‐return' (GSR) continuum, and its linkages with the above‐ground leaf economics spectrum (LES) and the below‐ground mycorrhizal association remain unclear. Here, we present the first empirical evidence of a direct link among multiple nutrient‐associated processes and tested this continuum hypothesis by synchronously integrating root nutrient absorption, leaf nutrient resorption and leaf litter decomposition of 15 co‐occurring tree species hosting either arbuscular mycorrhizal or ectomycorrhizal fungi in subtropical forests of China. Across species, there was an active trade‐off between phosphorus (P) absorption and resorption, which further caused a passive trade‐off between P resorption and leaf litter decomposition, indicating that the GSR continuum exists and runs on P economy. However, these processes associated with nitrogen economy were not well linked. Interestingly, the loading scores of species on the LES were positively correlated with root P absorption, negatively with leaf P resorption and positively with leaf litter decomposition. These linkages indicate that species running in the 'fast lane' had greater root P absorption, lower leaf P resorption and faster leaf litter decomposition than species running in the 'slow lane', and that the process‐based GSR continuum follows the trait‐based 'fast‐slow' LES. Furthermore, the continuum on P economy emerged evidently in the ectomycorrhizal tree species rather than in the arbuscular mycorrhizal tree species, indicating critical control of mycorrhizal association over the continuum. Synthesis. Overall, these results demonstrate the existence of the GSR continuum on tree P economy, which conforms to the economics spectrum theory but varies with mycorrhizal association type. Our findings provide a process‐based framework for mechanistic understanding of the whole plant nutrient economy and ecosystem nutrient cycling, and facilitate improved predictions of biogeochemical models. Abstract : Conceptual framework for the 'get‐save‐return' process continuum that comprises an active trade‐off between root nutrient absorption and leaf nutrient resorption as well as a passive trade‐off between leaf nutrient resorption and leaf litter decomposition. Acquisitive‐strategy species running in the 'fast lane' get more nutrients, resorb less nutrients, and return nutrients fast. Conservative‐strategy species running in the 'slow lane' get less nutrients, resorb more nutrients, and return nutrients slowly.